Victoria. The complete first season [videorecording (DVD)] - Coleman, Jenna, 1986-; Hughes, Tom, 1986-; Sewell, Rufus, 1967-; Firth, Peter, 1953- (2016)
In 1837, a diminutive, neglected teenager is crowned Queen Victoria, navigates the scandal, corruption, and political intrigues of the Court, and soon rises to become the most powerful woman in the world.